La agresividad y su relación con la autoestima en adolescentes (2020)
This monograph deals with "Aggression and its relationship with self-esteem in adolescents." It is important to analyze the aggressive behaviors of adolescents, for this a documentary review was carried out. The methodological design was framed within a qualitative approach, based on a Descriptive type of research The results of this research coincide with some studies in which it is concluded that there is a significant relationship between self-esteem and school aggressiveness. It is concluded that an active participation of parents in the social and affective learning of their children allows to minimize aggressive behaviors.